Making development happen - Urban Development Corporation (Kingston : Urban Development Corporation, 1992)
Done by the Urban Development Corporation in 1992 showing a photograph of fishermen at Bluefields beach in Westmoreland, Jamaica.
Keywords: Urban Development Corporation; Calendars -- Jamaica